RMR in Urban Tunnel with Risk Factor of Collapse - Jang, Hyong Doo; Yang, H. (Korean Society for Rock Mechanics, 2010)
RMR is a largely accepted rock classification method for design of support system in domestic tunnels. However, the RMR system, which is based on geological survey during design stage of tunnel, can not present the real ground conditions accurately. In this study, authors suggests a concept of Weighted-RMR (W-RMR), which considers weighted value of risk factors of collapse to prevent collapse and roof falls during tunneling. By implementing of W-RMR to Bye-Gye tunnel, the support and design flexibility is entailed giving due cognizance to the structural and geological features of the upper part of tunnel face.